PENGARUH KOMPENSASI LANGSUNG DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PT. SEMEN BATURAJA (PERSERO), TBK - Fitria Margaretha; Badia Perizade; Marlina Widiyanti; Zunaidah Zunaidah (The Manager Review, 2020)
This research aims to determine the effect of direct compensation and work discipline on the performance of employees at PT Semen Baturaja (Persero), Tbk. The population in this study is all employees of PT Semen Baturaja (Persero), TBK, 2020 as many as 894 employees. The samples used in the study were as many as 231 employees as respondents (Echelon 2, Echelon 3 and Echelon 5) obtained through purposive sampling techniques and combined with random sampling techniques. Data collection methods use questionnaires and data processing techniques used through multiple linear regression analyses. Results of multiple linear regression analyses showed that direct compensation has a positive and significant effect on the employee's performance at PT Semen Baturaja (Persero), TBK as well as the working discipline is positive and significant to the employee's performance at PT Semen Baturaja (Persero), TBK. Direct compensation needs to be optimize especially in terms of providing employee incentives and work discipline that needs to be improved by enforcing.